At Ford, turnaround is job one - Shein, James B., 1942- (SAGE knowledge. Cases., 2016)
The case opens with the Ford Motor Company seemingly on the path toward bankruptcy. Ford had been bleeding red ink for more than ten years when it decided in 2006 that continuing the same turnaround attempts was not going to right the ship. The company was facing significant external challenges, such as intense competition and changing consumer preferences, as well as internal challenges, such as quality and design issues and a stifling level of corporate complexity. As the case begins, CEO Bill Ford has taken the unusual step of hiring an auto industry outsider as his replacement. Alan Mulally, a thirty-seven-year Boeing veteran and principal architect of the venerable airplane manufacturer's own massive and successful turnaround, wasted little time in getting to know the business.